Anaerobic digestate management / Vinay Kumar Tyagi, Kaoutar Aboudi and Cidgdem Eskicioglu. - Tyagi, Vinay Kumar; Aboudi, Kaoutar; Eskicioglu, Cigdem (IWA Publishing, 2022)
"The book aims to analyse and discuss the conventional and emerging treatments of digestate generated in the anaerobic treatment of organic waste. Thus, in the circular economy framework, the book will address up-to-date strategies for the treatment and resource recovery from anaerobic digestate. Anaerobic digestion is an expanding technology nowadays, especially when considering the thrust in ongoing research on the value-added products and energy recovery from biomass wastes, i.e., sludges, agro-industrial waste, animal waste, food waste and organic fraction of municipal solid waste, etc. Anaerobic digestate is a leftover and waste management authorities across the world do not have so many options for digestate management except using the digestate for land application as a fertilizer or composting. However, researchers and field engineers are still looking for robust options for digestate management. Thus, a timely book on digestate management will be an invaluable addition to this domain. The key features of the book include : the broad range of biomass waste covered, discussion of conventional to advanced technological options, and the inclusion of successful case studies."--taken from back cover.